2005
DOI: 10.1213/01.ane.0000149548.88029.a2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Posture and Baricity on the Spread of Intrathecal Bupivacaine for Elective Cesarean Delivery

Abstract: Posture and baricity during induction of spinal anesthesia with intrathecal drugs are believed to be important in determining spread within the cerebrospinal fluid. In this double-blind prospective study, 150 patients undergoing elective cesarean delivery were randomized to receive a hyperbaric, isobaric, or hypobaric intrathecal solution of 10 mg bupivacaine during spinal anesthesia induced in either the sitting or right lateral position. After an intrathecal injection using a combined-spinal technique patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
62
1
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 15 publications
5
62
1
5
Order By: Relevance
“…In studies, in which hemodynamic effects of maternal position was compared, independent from the severity of hypotension, 1-and 5-minutes Apgar scores are similar in lateral and sitting positions (11,18,19,21,23). Similarly, in our study, besides no difference was found between the groups, none of the newborns had a 1-and 5-minutes Apgar score <7.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In studies, in which hemodynamic effects of maternal position was compared, independent from the severity of hypotension, 1-and 5-minutes Apgar scores are similar in lateral and sitting positions (11,18,19,21,23). Similarly, in our study, besides no difference was found between the groups, none of the newborns had a 1-and 5-minutes Apgar score <7.…”
Section: Discussionsupporting
confidence: 74%
“…Spinal anaesthesia using the same local anaesthetic agent in the same dose and volume can lead to different levels of sensory block according to the changes in the baricity of the local anaesthetic agent. Hallworth and colleagues (21) in their study evaluating the effects of 10 mg hyperbaric, isobaric and hypobaric bupivacaine forms on the mother's position and hemodynamic characteristics, found the mean maximum sensory block level in sitting and lateral positions as T3 in the hyperbaric groups, and T2 in the isobaric and hypobaric groups. In the hyperbaric group, there were 3 patients (12%) with cervical dermatome involvement in the lateral position; however, none of the patients in sitting position had cervical dermatome involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in SBP could be explained in part by the rapid cephalad spread of the local anesthetic and the accompanying sympathectomy 12,15 and in part by aortocaval compression caused by the gravid uterus despite the 15°left tilt that was used in all patients. A study by Rees et al 16 supports these findings; they showed that even a true 15°left table tilt is associated with some aortic compression.…”
Section: Discussionmentioning
confidence: 99%
“…There were no differences in systolic blood pressure (P = 0.127) or heart rate (P = 0.831) over time between groups. Time to a modified Bromage score of 2 was longer in Group S than in Group L [101 (15) min vs 88 (14) min, respectively; P \ 0.001]. Conclusions Sitting the patient up for five minutes rather than laying the patient down immediately after spinal anesthesia for Cesarean delivery decreased intraoperative sensory block height, ephedrine and fluid requirements, and intraoperative nausea, vomiting, and shortness of breath without affecting systolic blood pressure or the success of the anesthetic.…”
Section: Introductionmentioning
confidence: 97%
“…In a study examining the effects of posture and baricity on spinal anesthesia, Hallworth et al added 1.6 mL normal saline and 0.4 mL D5W to 8 mL of 0.5% bupivacaine to make an isobaric solution as measured by a density meter. 4 A more easily obtained local anesthetic solution isobaric to CSF in pregnancy is 1% tetracaine in water. 5,6 It is prepared by adding 2 mL sterile water to a 20 mg ampoule of lyophilized tetracaine.…”
mentioning
confidence: 99%